Evaluación de la operación en la unidad de destilación de un complejo de aromáticos para condiciones operacionales diferentes al diseño (2018)
The aromatics complex is based on the processing of low octane naphtha and low aromatics content to transform it into high octane gasoline and high aromatic content; counting with different units that are responsible for carrying out this process through the use of debutanized naphtha obtained from the atmospheric distillation of crude oil. However, the use of heavy naphtha from hydrocracking processes allows to generate additional economic benefits for the company due to the increase in the production of aromatics that are marketed mainly internationally, therefore, the modification of the raw material is proposed of charge to the reformer of the complex for the production of aromatics.